DEVELOPING STUDENT’S ABILITY TO HOLD A DISCOURSE THROUGH DIALOGUES - Munira Xabibullayevna Xakimova,; Ilhamova Nigina,; Bahadirova Muxlisa, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The importance of dialogue in forming students' communication cultures and its critical role in the development of their discursive skills are examined in this essay. Effective strategies for improving abilities including logical reasoning processes, understanding the viewpoints of others, and responding appropriately to others during communication are examined in this study. The report also provides useful advice on how to use contemporary pedagogical technology to improve students' overall discursive ability and prepare them for spontaneous conversation. The results highlight how important deliberate dialogic practices are for improving students' critical thinking, communication, and teamwork skills. This study adds to the continuing conversation on effective teaching methods for fostering students' ability to have fruitful conversations, enabling them to take an active role in their education and in larger social interactions.This study adds to the continuing conversation on effective teaching methods for fostering students' ability to have fruitful conversations, enabling them to take an active role in their education and in larger social interactions. For two main reasons, discourse skills—which include both competent speaking and listening—are essential to a successful education. Students can clarify their opinions, hear other people's viewpoints, and work through difficult ideas through conversations and debates.